Bates' nursing guide to physical examination and history taking - Hogan-Quigley, Beth; Bates, Barbara , 1928-2002; Bickley, Lynn S.; Palm, Mary Louise (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Accompanied by a Lab Manual that incorporates nursing-specific case studies to reinforce content from a nursing perspective. This book can be packaged with the Bates for Nursing Online course for a complete nursing assessment solution